COMMUNITY SERVICE THROUGH EMPOWERMENT OF MSMES TO IMPROVE COMMUNITY ECONOMY IN JAMBO MESJID VILLAGE, BLANG MANGAT DISTRICT - Ismuhadi; Intan Maulida; Rahmiatul Aula; Raudhatinur; Almunadiya; Muhadar (RADJA PUBLIKA, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are businesses run by individuals or groups to improve the community's economy. This economic improvement can be achieved through empowering existing MSMEs. The student community service program is carried out through MSME empowerment, namely the establishment of an MSME management structure in Jambo Mesjid Village, Blang Mangat District. The goal of this service is to improve the community's economy and enhance the quality of human resources. Several other activities are also carried out, such as assistance with halal certification for MSME products, marketing outreach, and the organization of an MSME bazaar in Lhokseumawe City. The program implements the Asset-Based Community Development (ABCD) method, which focuses on community potential and assets. The results of this service are the formation of MSME groups and direct training through participation in the Lhokseumawe City Festival Sunday Bazaar. This program is intended to be sustainable and improve the economy of the community in Jambo Mesjid Village, Blang Mangat District.